Making Good Women - Abena Kyere (African Journal of Gender and Religion (AJGR))
There is a vast body of literature on how Africans have historically interacted with Christianity. One area in the discourse claims that Christianity and its extension, western education, shaped and in some cases succeeded in changing the gendered ideals and the very social fabric of society. This article deepens and adds nuance to the argument that missionary education shaped young women into prospective wives for clergymen in Ghana. Examining various works of literature, archival materials and in-depth interviews, the article reconstructs the trajectory of the clergy-wife position and concludes that missionary education aimed to remold the gendered spaces of Ghanaian society through the education of girls. However, this missionary ideal of a good woman who exemplified all the tenets of a godly Christian wife was to be found in the Clergy wife (CW). The paper concludes that the CW position led to the creation of a privileged class of women and, thus, through this creation, the missionary project of creating an ideal woman could be deemed successful.